Deficiencies in reporting inclusion/exclusion criteria and characteristics of patients in randomized controlled trials of therapeutic interventions in pressure injuries: a systematic methodological review - Miranda, Jéssica Steffany; Abbade, Luciana P. F. [UNESP]; Abbade, Joelcio Francisco [UNESP]; Thabane, Lehana; Mbuagbaw, Lawrence; Pascon, Gisele Chicone; Campanili, Ticiane Carolina Gonçalves Faustino; Santos, Larissa Paula; de Gouveia Santos, Vera Lúcia Conceição (Wiley, 2024)
Wound care is a complex procedure and the related research may include many variables. Deficiencies in the sample inclusion and exclusion criteria may limit the generalizability of randomized controlled trials (RCTs) for wound patients in the real world. This study aimed to evaluate deficiencies in reporting the inclusion and exclusion criteria and the characteristics of patients in RCTs of pressure injuries (PI) therapeutic interventions. We conducted a systematic methodological review in which 40 full text RCTs of PI treatment interventions published in English, from 2008 to 2020, were identified. Data on the general characteristics of the included RCTs and data about inclusion/exclusion criteria and characteristics of patients were collected. The inclusion/exclusion criteria were categorized into five domains (definition of disease, precision, safety, ethical/legal and administrative). Study duration (in weeks) was 8.0 (quartile 1: 2.0; quartile 3: 48.0); only 5.0% of the trials mentioned race, skin colour or ethnicity, and 37.5% reported the duration of the wound. Only 9 (22.5%) studies reported the drugs that the included patients were using and 10 (25.0%) RCTs reported adverse events. The presence of the five domains was observed only in 12.5% of RCTs and only 12 (30.0%) had the precision domain. Much more research is required in systematic assessments of the external validity of trials because there is substantial disparity between the information that is provided by RCTs and the information that is required by clinicians. We concluded that there are deficiencies in reporting of data related to inclusion/exclusion criteria and characteristics of patients of RCTs assessing PI therapeutic interventions.
Keywords: pressure injury; randomized clinical trial; review; treatment outcome; validity of results